Highly sensitive and reliable human sex determination using multiplex PCR - Junaida Osman,; Nor Azian Abdul Murad,; Chin, Siok-Fong; Rahman Jamal, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2014)
Gender validation is indispensable in data verification for demographic information particularly in large-scale population studies and also as part of the quality assurance of biospecimen repositories. Gender validation is also critical as part of quality control processes before specimens are subjected to sequencing analysis to identify germline and somatic mutations. The SRY gene is considered a useful signature gene marker that differentiates male from female. The aim of the study was to validate the SRY gene marker for use in gender determination in large cohort studies. SRY gene-specific sequences were amplified by PCRCR, electrophoresed on agarose gels and the 254 bp band was visualized for male samples. A series of DN A template concentrations were tested for sensitivity determination. The reaction was validated on 48 gender-blinded samples obtained from the UMBI BioBank to determine the specificity. ATL1 gene-specific sequence on X chromosome was used as the internal control. This PCR method has demonstrated 100% gender specificity. The sensitivity of the reaction was demonstrated with as low as 0.1 ng male DN A. The findings had suggested that SRY analysis by Multiplex PCR is a highly sensitive and specific method for gender determination and can be extremely useful for large-scale samples.